[Hermes Trismegistos] Stobaei Hermetica XI (Ioannis Stobaei Anthologium: Hermetica, excerptum XI) - Sowińska, Agata Ewa (Vox Patrum, 2022)
Translation of the Ioannis Stobaei Anthologium: Hermetica, excerptum XI into Polish.